El discurso del amor en tres compositoras de canción popular, 1940-1950, ciudad de México. - Ramírez Roa, Angélica. (University of Ottawa (Canada), 2002)
The aim of this investigation is to analyze texts by women composers of popular songs, in particular those by Maria Grever, Consuelo Velazquez and Emma Elena Valdelamar, written between 1930 and 1950 in Mexico. In the first chapter we discuss the way these women conceive love as a gender subject. We first define the concept of gender as well as some aspects of the language they use in relation to gender. Then we focus on the role of the women composers in Western tradition music, particularly Mexican women composers of popular songs. In the second chapter, we analyze the concept of popular song, discussing its origins and influences. We attempt a classification by theme. This allows us to establish the cultural historic framework delimited as the urban song of love. In the third chapter, we discuss the concepts of metaphor, metonymy and synecdoque (following Lakoff and Johnson understanding of this concept), to arrive at a definition of a general metaphor, i.e the way the three women composers understand the concept of love. To achieve this goal we allude to the body conception, the concrete action of love-making, the kiss, the opposition between love and reason, jealousy and destiny. To conclude, we explore the differences in language used by women composers and men composers of this period.
Keywords: Language, Modern.